Genome-based reclassification of Azospirillum brasilense Az39 as the type strain of Azospirillum argentinense sp. nov. - dos Santos Ferreira, Natália; Coniglio, Nayla Anahí; Puente, Mariana Laura; Sant’Anna, Fernando Hayashi; Maroniche, Guillermo Andrés; Garcia, Julia Elena; Molina, Romina Micaela; Nievas, Sofía; Volpiano, Camila Gazolla; Ambrosini, Adriana; Passaglia, Luciane Maria Pereira; Pedraza, Raúl Osvaldo; et al. (Microbiology Society, 2023)
Strain Az39T of Azospirillum is a diazotrophic plant growth-promoting bacterium isolated in 1982 from the roots of wheat plants growing in Marcos Juárez, Córdoba, Argentina. It produces indole-3- acetic acid in the presence of l-tryptophan as a precursor, grows at 20–38 °C (optimal 38 °C), and the cells are curved or spiral-shaped, with diameters ranging from 0.5–0.9 to 1.8–2.2 μm. They contain C16 : 0, C18 : 0 and C18 : 1 ω7c/ω6c as the main fatty acids. Phylogenetic analysis of its 16S rRNA gene sequence confirmed that this strain belongs to the genus Azospirillum, showing a close relationship with Azospirillum baldaniorum Sp245T, Azospirillum brasilense Sp7T and Azospirillum formosense CC-Nfb- 7T. Housekeeping gene analysis revealed that Az39T, together with five strains of the genus (Az19, REC3, BR 11975, MTCC4035 and MTCC4036), form a cluster apart from A. baldaniorum Sp245T, A. brasilense Sp7T and A. formosense CC-Nfb- 7T. Average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) between Az39T and the aforementioned type strains revealed values below 96 %, the circumscription limit for the species delineation (ANI: 95.3, 94.1 and 94.0 %; dDDH: 62.9, 56.3 and 55.6 %). Furthermore, a phylogeny evaluation of the core proteome, including 809 common shared proteins, showed an independent grouping of Az39T, Az19, REC3, BR 11975, MTCC4035 and MTCC4036. The G+C content in the genomic DNA of these six strains varied from 68.3 to 68.5 %. Based on the combined phylogenetic, genomic and phenotypic characterization presented here, we consider that strain Az39T, along with strains Az19, REC3, BR 11975, MTCC4035 and MTCC4036, are members of a new Azospirillum species, for which the name Azospirillum argentinense sp. nov. is proposed. The type strain is Az39T (=LBPCV39T=BR 148428T=CCCT 22.01T).